Distributive justice : a comparative analysis - Sulaiman, Kabuye Uthman (2011)
Distribution of wealth and income is one of the most important topics concerning the economic life of man, and yet the most controversial. It is due to distribution of wealth and income that great revolutions such as the French Revolution of 1789, and armed conflicts in many parts of the world have taken place. The most fundamental question 86 in the distribution of wealth and income is: What criterion or criteria should be followed to achieve distributive justice'} This question has been a big controversy among philosophers, economists. and politicians, and no conclusion has ever been reached. In this paper I intend to analyze, comprehensively and systematically, the 'Islamic Theory' of distributive justice in comparison with the 'Entitlement Theory' and the 'Difference Principle' so as to show the differences and similarities between it and these two liberal theories of distributive justice that now dominate the Western thought. The study will be limited to views offour contemporary thinkers; namely, Sayyid Qutb, Muhammad Baqir al-Sadr, John Rawls and Robert Nozick. The fanner two are recognized figures in the contemporary Islamic thought. They have addressed themselves to social, political, cultural and economic problems prevalent among contemporary Muslims and have suggested some ways to overcome them, based on the teachings of the Qur'an and Sunnah. The two are regarded among the pioneers ofIslamic revival, which is concerned mainly with the establishment of an Islamic State, and the application of the Shari'ah (Islamic law) in all aspects of life. Ibn HaIdun